2021
DOI: 10.1155/2021/4982227
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Lineage Contribution of PDGFRα‐Expressing Cells in the Developing Mouse Eye

Abstract: PDGFRα signaling is critically important in ocular development. Previous data on PDGFRα lacks an expression map with high spatial and temporal resolution and lineage information. In this study, we aim to present a detailed PDGFRα expression and lineage map from early embryogenesis to adulthood. PDGFRα-CreER; mT/mG reporter mice were analyzed. mEGFP-positive cells contributed to multiple ocular lineages in a spatiotemporally regulated manner. A dynamic PDGFRα expression was identified in corneal stromal cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…PDGFRA signaling is associated with many physiological processes, such as embryonic development, cell proliferation, differentiation, migration, and survival, and is critical for organogenesis, including the development of the lung, intestine, skin, testis, and kidney 19 , 20 . PDGFRA signaling also plays a critical function in the development of ocular tissues such as the cornea, lens, and optic nerve 19 , 21 , 22 . Several studies have reported that its signaling is involved in corneal fibroblast migration and proliferation, which are fundamental processes for corneal wound healing 23 – 26 .…”
Section: Discussionmentioning
confidence: 99%
“…PDGFRA signaling is associated with many physiological processes, such as embryonic development, cell proliferation, differentiation, migration, and survival, and is critical for organogenesis, including the development of the lung, intestine, skin, testis, and kidney 19 , 20 . PDGFRA signaling also plays a critical function in the development of ocular tissues such as the cornea, lens, and optic nerve 19 , 21 , 22 . Several studies have reported that its signaling is involved in corneal fibroblast migration and proliferation, which are fundamental processes for corneal wound healing 23 – 26 .…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%